An experience of practitioners navigating the role of patient/caregiver - Susan Shaw (The Beryl Institute, 2017)
This journey involved one of us having (repeat) intraspinal surgery in a country far from home but of a similar culture and with the same first language. The carer travelled across the world to be present during the hospital stay. We kept a journal during our admission, and following discharge realised there were significant differences between how we had documented our experience and the record presented in the clinical notes. The particular examples we present illustrate the relationships, rules and issues that we navigated. We share our experience in the form of moments from our journal, some of them alongside information recorded in the clinical notes for the corresponding timeframe. This provides insights into differing narratives between the experiences of the patient/caregiver and practitioners. We recommend that individual practitioners and organisations consider the lived experience of patients and how they consciously engage with patients/carers to address the risk of ‘othering’.